Social Media Monetisation: Ethical Challenges and the Role of Media Literacy in the Digital Era - Suardi; Ida Bagus Putu Suamba (Soshum: Jurnal Sosial dan Humaniora, 2025)
The proliferation of social media platforms has created substantial opportunities for digital content monetisation, fundamentally transforming the digital economy. However, this growth is accompanied by complex ethical challenges, including concerns over content authenticity, user privacy, and adverse psychological and social impacts. This study investigates these ethical dilemmas and evaluates the role of media literacy in fostering responsible digital content management. Employing a qualitative methodology, the research integrates content analysis of diverse social media platforms with in-depth interviews involving active users and media literacy experts. The findings indicate that monetisation practices frequently compromise content integrity and user well-being, underscoring the urgent need for enhanced media literacy. The study concludes that a collaborative approach—engaging platforms, users, and educational institutions—is essential to strengthen media literacy and promote ethical engagement in the digital era.